Linc00483 as ceRNA regulates proliferation and apoptosis through activating MAPKs in gastric cancer. Issue 8 (15th May 2018) - Li, Defeng; Yang, Meifeng; Liao, Aijun; Zeng, Bing; Liu, Diqun; Yao, Yuhong; Hu, Guangsheng; Chen, Xuanmin; Feng, Zhiqiang; Du, Yanlei; Zhou, Youlian; He, Jie; et al.
Abstract: Long non‐coding RNAs (lncRNAs) are important regulators of many cellular processes, and their aberrant expression and/or function is associated with many different diseases, including cancer. However, the identification of functional lncRNAs in gastric cancer is still a challenge. In this study, we describe a novel functional lncRNA, linc00483, that is upregulated and associated with tumorigenesis, tumour size, metastasis and poor prognosis in gastric cancer. In our study, linc00483 promoted gastric cancer cell proliferation, invasiveness and metastasis in vitro and in vivo. Mechanistically, upregulated expression of linc00483 in gastric cancer acts as a sponge to absorb endogenous tumour suppressor miR‐30a‐3p. Furthermore, it restores SPAG9 expression, which is negatively regulated by miR‐30a‐3p, and actives MAPK signaling pathway in gastric cancer cells. Thus, linc00483 is an oncogenic lncRNA in gastric cancer and targeting linc00483 or its pathway can potentially be useful in development of targeted therapies for patients with gastric cancer. Our results show that linc00483 is an important regulator in carcinogenesis and may be a useful biomarker to predict prognosis of gastric cancer patients. We believe our findings are novel and will be of interest to scientists working in many areas related to biomarkers in cancer.